Tijolos ecológicos: estudo de viabilidade técnica no uso de agregados reciclados de resíduos da construção civil classe A - Lira, Douglas Sadalla de (2020)
Currently, the construction sector occupies a prominent place in the world when it comes to waste generation, the activities of this sector produce impacts that permeate from the extraction of raw material to what to do with the waste resulting from its activities in view of this. this sector acts directly on the environment. Because civil construction spends a large amount of its natural resources on the planet and becomes one of the most notable sectors in terms of waste generation. Sustainable development emerges for the sector as a factor of cooperation to assist the civil construction sector in the socio-environmental problems generated by this range of construction waste - CW. Their disposal in an irregular or clandestine way in the environment and in the municipalities, act environmentally and afflict public health because the CW. residues serve as breeding grounds and proliferation of diseases caused by vectors that end up staying in this waste. The sector is the target of several criticisms and discussions. In this sense, recycling techniques for this CW have emerged, making possible their reuse with a view to meeting public policies, resolutions, laws and standards. Current policies demand that society take immediate action for future generations and thus the questions of sustainable development. The CW presents itself in many Brazilian municipalities as a factor of serious problems. In this sense, the use of recycled class A CW in the incorporation of ecological bricks was addressed, thus stimulating the reinsertion of the waste in the market and thus collaborating with the principle’s sustainability. Based on a bibliographic research and a field research, where, composed of technical visits to an ecological brick factory which makes use of recycled CW as an input in production. The STS perspective brings a broader perspective to the construction sector, where society and the environment are key factors in leveraging the reuse of CW. It is concluded that in order to have a sustainable construction, it is necessary the commitment and awareness of the parties involved in the generation of CW about the forms of final disposal and the existing technologies capable of reinserting the RCC in the market. The present work found through the tests described in ABNT NBR 8491:2012, that the incorporation of recycled class A CW as raw material in ecological bricks for use in sealing masonry, met the normative requirements and requirements, obtaining in the compression test simple the average of 5.75 MPa and in the water absorption test the average of 13.08%, thus demonstrating to society that these bricks corroborate the requirements of sustainability and can contribute to a better world for future generations.